Preliminary In Vitro Evaluation of the Probiotic Potential of the Bacteriocinogenic Strain Enterococcus lactis PMD74 Isolated from Ezine Cheese - Başar Uymaz Tezel (Journal of Food Quality)
Ezine cheese is a nonstarter and long-ripened cheese produced in the Mount of Ida region of Çanakkale, Turkey, with a protected designation of origin (PDO) status. The nonstarter fermented foods serve as sources for the isolation of novel strains. The present study aimed to report the novelty of the bacteriocinogenic Enterococcus lactis PMD74 strain and the in vitro assessment of its potential as a probiotic candidate. Additionally, the present study aimed to describe the technological and safety-related properties of the aforementioned strain. The strain exhibited high viability at pH 3.0, in the presence of pepsin, pancreatin, and bile salts (0.3% and 0.5%), and considerable survival passage through the stimulated digestion tests. The strain PMD74 exhibited substantial autoaggregative (41%) and coaggregative properties, which increased as a function of time. The highest coaggregation percentage was obtained with Salmonella enterica serotype Typhimurium SL1344 (23%), followed by Staphylococcus aureus ATCC 6538 (10.3%) and Escherichia coli ATCC 26922 (7.4%), respectively. The strain PMD74 was able to inhibit the growth of a number of Gram-positive bacteria, including Listeria monocytogenes, Lactobacillus sake, Staphylococcus aureus, and E. faecalis. The antimicrobial activity of the proteinaceous compound was calculated as 6400 AU·mL−1 by the critical dilution method against E. faecalis ATTC 29212. γ-Hemolytic PMD74 was observed to be sensitive to vancomycin, ampicillin, penicillin, gentamicin, tetracycline, chloramphenicol, and tylosin. Among the four genes tested, E. lactis PMD74 was observed to be positive for three virulence determinants, ace, sprE, and gelE, and negative for esp. The amino acid decarboxylase activities were detected negative for histidine, tyrosine, and ornithine. E. lactis PMD74 was classified as a low acidifier, which suggested its possible role as an adjunct culture. E. lactis PMD74 exhibited considerable survival ability (8.86 log CFU·mL−1) in the acidic condition of fermented milk for a four-week-long storage period.